Evolution of forest precipitation water storage measurement methods. Issue 11 (27th November 2014) - Friesen, Jan; Lundquist, Jessica; Van Stan, John T.
Abstract Precipitation intercepted by forests plays a major role in more than one‐fourth of the global land area's hydrologic cycle. Direct in situ measurement of intercepted precipitation is challenging, and thus, it is typically indirectly estimated through comparing precipitation under forest cover and in the open. We discuss/compare measurement methods for forest precipitation interception beyond classical budgeting and then recommend future directions for improving water storage estimation. Comparison of techniques shows that methods submerging tree components produce the largest water storage capacity values. Whole‐tree lysimeters have been used with great success at quantifying water storage for the integrated system yet are unable to separate trunk versus canopy storage. Remote sensing, particularly signal attenuation, may permit this separation. Mechanical displacement methods show great promise and variety of techniques: pulley/spring system, branch strain sensors, trunk compression sensors and photography. Relating wind sway to water storage also shows great promise with negligible environmental disruption yet is currently at the proof‐of‐concept stage. Suggested future directions focus on development of common features regarding all discussed methods: (i) measurement uncertainties or processes beyond interception influencing the observed signal, (ii) scaling approaches to move from single tree components to the single‐tree and forest scales and (iii) temporal scaling to estimate the relevance of single‐interception components over longer timescales. Through addressing these research needs, we hope the scientific community can develop an 'integrated' monitoring plan incorporating multiple measurement techniques to characterize forest‐scale water storage dynamics while simultaneously investigating underlying (smaller‐scale) components driving those dynamics across the spectrum of precipitation and forest conditions. Copyright © 2014 John Wiley & Sons, Ltd.